2010
DOI: 10.1021/ja104672n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Electrolysis Catalysts on Carbon Corrosion in Polymer Electrolyte Membrane Fuel Cells

Abstract: A new approach to preventing electrochemical carbon corrosion in the cathode of polymer electrolyte membrane fuel cells (PEMFCs) was developed. The addition of 2 wt % IrO(2) (0.016 mg cm(-2)) to the catalyst layer of the cathode was demonstrated to reduce the electrochemical corrosion of carbon by 76% at 1.6 V(NHE) and 70 °C compared with a commercial Pt/C catalyst of the same Pt loading of 0.4 mg cm(-2) and under the same test conditions. The IrO(2) was shown to behave as a catalyst for water electrolysis, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 14 publications
0
79
0
Order By: Relevance
“…This is due to the corrosion of carbon above 1.6 V vs NHE, as verifi ed by CO 2 mass spectrum. [ 72 ] The carbon corrosion was suppressed when the IrO 2 loading was 1.2 mg cm −2 , as indicated by the linear relationship between the cell voltage and current density. The suppression of carbon corrosion was due to two reasons.…”
Section: Catalyst Selectionmentioning
confidence: 95%
See 2 more Smart Citations
“…This is due to the corrosion of carbon above 1.6 V vs NHE, as verifi ed by CO 2 mass spectrum. [ 72 ] The carbon corrosion was suppressed when the IrO 2 loading was 1.2 mg cm −2 , as indicated by the linear relationship between the cell voltage and current density. The suppression of carbon corrosion was due to two reasons.…”
Section: Catalyst Selectionmentioning
confidence: 95%
“…[ 72 ] Hybrid Li-air cells with varying amounts of LiOH in the catholyte have also been studied by Zhou et al [ 77 ] They found that the cell voltage and the internal resistance decrease with an increasing concentration of LiOH. The cell voltage is related to the ratio of OH − /O 2 , obeying the Nernst equation.…”
Section: Catholyte Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jang et al [67] studied the effect of water oxidation catalyst added into cathode to weaken carbon corrosion. In Figure 7, compared with commercialized Pt/C catalyst, the electrochemical carbon corrosion decreased by 76% with 2 wt % IrO 2 (0.016 mg·cm −2 ) under 1.6 V (vs. NHE) and 70 • C. CO 2 monitoring showed that the water oxidation catalyst had the effect of mitigating carbon corrosion.…”
Section: Water Oxidation Catalystmentioning
confidence: 99%
“…Some papers [16,67,68] proposed that the water oxidation catalyst has a positive effect on water electrolysis over and above carbon corrosion and the degradation of carbon support material. It is obvious that water oxidation catalyst improves the cell reversal tolerance with increasing effect (RuO 2 -IrO 2 > RuO 2 -TiO 2 > RuO 2 ).…”
Section: Water Oxidation Catalystmentioning
confidence: 99%